FISH FARMERS ATTITUDE TOWARDS GOVERNMENT ASSISTANCE IN AQUACULTURE OF TILAPIA (Oreocromis niloticus) IN PERHENTIAN LUAS VILLAGE, LOGAS TANAH DARAT DISTRICT, KUANTAN SINGINGI REGENCY, RIAU PROVINCE - Rima Putri; Kusai '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on 28 July to 14 August 2013 in the PerhentianLuas Village, Logas Tanah Darat District, Kuantan Singingi Regency, Riau Province.This research purposed to investigate the characteristics of fish farmers, knew theattitude of farmers towards government assistance, knew the relationship betweencharacteristics of multiple variables with farmers attitude towards governmentassistance. This research used survey method. Respondents in this research was fishfarmers who received government assistance.Results of farmers attitudes toward government aid analysis was mostly good,namely 64.29%. Farmers attitude towards farming activities also showed a goodattitude at 50.00%. Results of farmers attitude analysis with some characteristicsvariables obtained after correlated have known that the relationship between age didnot correlate perfectly to the assistance with rs 0.062 its smaller than the value of P(0.832). While on production value greater than (0.344) P (0.228) mean age hadeffect on tilapia farming activities. Education was not perfectly correlated to the aidand on production with a value of 0.125 Spearman rank correlation value less than P(0.670) and the value of correlation Spearman Rank. While income was not perfectlycorrelated to aid with rs 0.212, less than P value (0.466), as well as on aquacultureactivities, it’s smalleer than P (0.744) that’s mean income didn’t have effect onaquaculture.Kata Kunci : Attitude, Government assistance, Aquaculture.